A COMPARISON OF THE EFFECTIVENESS OF HEALTH EDUCATION METHODS ON ANXIETY LEVELS AMONG PRE-CATARACT SURGERY PATIENTS IN CENTRAL JAVA, INDONESIA - Wibawa, Shinta Restu; Suharjo, Suharjo; Rahmat, Ibrahim (Public Health of Indonesia, 2018)
Background: Not much is known about the impact of health education in reducing anxiety levels in pre-cataract surgery patients in Indonesia.Objective: The aim of this study was to compare the effectiveness of counseling and lecture methods using leaflet in reducing anxiety levels  among pre-cataract surgery patients in Central Java, Indonesia.Methods: This was quasi experiment with pretest- posttest design with two comparative groups at two hospitals in November 2014. It was 70 preoperative cataract patients selected using total sampling, which 35 randomly assigned to intervention group 1 and intervention group 2. The Analog Anxiety Scale (AAS) was used to measure anxiety levels. Data were analyzed using paired t-test and independent t-test.Results: There was a significant effect of health education using counseling and lecture method with leaflet media in reducing anxiety levels among preoperative cataract patients (p=.001). A counseling method was more effective than lecture method in dealing with anxiety levels (p=.001).Conclusion: Findings of this study can be used as a basis for development of nursing intervention in the hospital setting to reduce the anxiety levels among pre-cataract surgery patients.